MORPHOMETRICAL ANALYSIS OF STERNUM BONE FOR SEXUAL DIMORPHISM ESTIMATION– AN AUTOPSY BASED STUDY (Journal of Forensic Medicine & Toxicology, 2020)
Sexual dimorphism studies on bones relied on both morphological as well as morphometrical analysis. Apart from well established accuracies in skull and pelvis bones for sex differentiation, other bones of the human body were also assessed for same reason. This study was aimed to determine the sexual dimorphism characteristic of sternum bone by morphometrical analysis and also to compare the sex differentiation efficacy by different statistical methods. Length of manubrium (ML), length of mesosternum (MSL), combined length of manubrium and mesosternum (MBL) and sternal index (SI) were measured and calculated from 100 dried sternums of confirmed sex (56 male and 44 female) for sex differentiation in North Indian (Delhi) population. Significant statistical mean differences were observed between two sexes and on applying Discriminant function analysis (univariate and multivariate) along with Logistic regression analysis, 93- 95% and 94-95.6% of sternum were correctly classified respectively. The most reliable single measurement was length of mesosternum (MSL), with a classification rate of 95%, and sternal index was the least sexually dimorphic. Out of identification point, demarking point and limiting point; limiting point appears to be a more useful tool in sex differentiation of sternum. Sternum, thus emerge to be a good adjunct in ascertaining sex in an unknown subject.
Keywords: Sternum; Sexual Dimorphism; Morphometry; Discriminant Analysis; Logistic Regression Analysis